A LOOK AT THE HISTORY OF LEGAL ACTIVITY AND CULTURE FORMATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article discusses the role of legal education in the formation of legal activity and culture and the means of its implementation.